2013
DOI: 10.1016/j.jacc.2013.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitric Oxide on Cell Proliferation

Abstract: Nitric oxide (NO) has been suggested to be a pathophysiological modulator of cell proliferation, cell cycle arrest, and apoptosis. In this context, NO can exert opposite effects under diverse conditions. Indeed, several studies have indicated that low relative concentrations of NO seem to favor cell proliferation and antiapoptotic responses and higher levels of NO favor pathways inducing cell cycle arrest, mitochondria respiration, senescence, or apoptosis. Here we report the effects of NO on both promotion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(163 citation statements)
references
References 81 publications
4
146
0
4
Order By: Relevance
“…Although NO has also been reported to induce apoptosis in some studies, it is worth noting that this adverse effect may be due to the different dose of NO or exposure time used in the specific experiments (45,46). Based on cumulative studies to date, the discrepancy is now rather resolved and seems to indicate that NO has important roles in modulation of cell proliferation and antiapoptotic response at a low level and that a high level of NO likely induces the opposite effects (47). Thus, it is of the utmost importance to optimize dose and time for DETA-NO preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Although NO has also been reported to induce apoptosis in some studies, it is worth noting that this adverse effect may be due to the different dose of NO or exposure time used in the specific experiments (45,46). Based on cumulative studies to date, the discrepancy is now rather resolved and seems to indicate that NO has important roles in modulation of cell proliferation and antiapoptotic response at a low level and that a high level of NO likely induces the opposite effects (47). Thus, it is of the utmost importance to optimize dose and time for DETA-NO preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…fibroblasts, pancreatic tumors, myoblasts, keratinocytes, and endothelial cells, 28,30,31,37 whereas NO in the millimolar range inhibits cell proliferation. 29,38,39 The reason for this biphasic effect is not well understood, but it has been suggested that the NO-mediated increase in endothelial cell proliferation requires the production of reactive oxygen species, because superoxide dismutase and catalase suppress, in part, the stimulatory effect of NO on cell proliferation. 28,39 NO at a low concentration (1 mM) increases endothelial cell proliferation, 28 whereas NO at a high concentration (>100 mM) has no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Порушення регуляції та реалізації останнього є також основою для розвитку низки патологічних процесів. Більшість авторів схиляються до висновків, що розбіж-ності у спрямованості ефектів ендогенного оксиду азоту залежать не тільки від його вмісту та типу клітин, а також від актив-ності онкогенів і стадії клітинного циклу, тому цю молекулу вважають фізіологічним модулятором проходження клітинного циклу, проліферації та апоптозу [3].…”
Section: вступunclassified